Nanoparticle-mediated defense and antiviral protection in roselle against Hibiscus chlorotic ringspot virus (HCRSV) - Abdelkader, Hayam Samy; Kheder, Ahmed A.; Farroh, Khaled Yehia; Shfie, Radwa Mahmoud (Journal of Plant Protection Research, 2026)
Hibiscus sabdariffa (roselle) is highly susceptible to Hibiscus chlorotic ringspot virus (HCRSV), for which effective control strategies remain limited. This study assessed the antiviral and defense-priming potential of foliar-applied chitosan–silver nanocomposites (CS-Ag NCs) and copper oxide nanoparticles (CuO-NPs) at concentrations of 50–300 ppm, applied either before or after virus inoculation. The nanomaterials were synthesized and physicochemically characterized using HR-TEM, DLS/ζ-potential, and XRD analyses. Both CS-Ag NCs and CuO-NPs significantly reduced HCRSV infection incidence in a dose-dependent manner, with the strongest curative effects observed at 300 ppm post-inoculation (CS-Ag ≈ 91.7% and CuO ≈ 85%), without visible phytotoxic effects under greenhouse conditions. CS-Ag NC treatment markedly enhanced host defense capacity, as reflected by increased activities of antioxidant and phenylpropanoid-related enzymes (PAL, POX, and CAT), elevated phenolic and anthocyanin contents, and improved sepal yield (222.6 g plant⁻¹ compared to 133.2 g plant⁻¹ in infected controls). Gene-expression profiling (2⁻ΔΔCt) revealed strong CS-Ag-mediated induction of sulfur redox–associated genes, particularly sulfite oxidase (SO) and APS kinase (APK), indicating reinforcement of redox homeostasis and reactive oxygen species detoxification pathways. In contrast, adenylylsulfate reductase (APR) exhibited a biphasic, dose-dependent transcriptional response, suggesting that sulfur assimilation is finely regulated and sensitive to both nanomaterial type and stress intensity. Collectively, these findings indicate that CS-Ag NCs predominantly act as defense-priming agents that enhance sulfur-linked antioxidant signaling, whereas CuO-NPs confer antiviral protection in a more dose- and stress-dependent manner. This study provides mechanistic insight into nano-enabled antiviral defense in roselle and identifies practical dose–timing windows for disease management, while underscoring the need for field-level validation and environmental safety assessment prior to large-scale application.